Application Of IFRS 5 And PSAK 58 On Non-Current Assets Held For Sale And Discontinued Operations: A Literature Review - Ardiansyah Ardiansyah; Ecliza Novianti; Wiwik Pratiwi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to provide an in-depth examination of the implementation of IFRS 5 and PSAK 58 concerning non-current assets held for sale and discontinued operations, using a systematic literature review approach. The research adopts a qualitative descriptive method with thematic analysis techniques applied to academic journals, accounting standards, and empirical findings. The grand theory employed is the Value Relevance Theory, which asserts that high-quality accounting information is reflected in the market value of firms, supported by the Positive Accounting Theory to understand managerial incentives behind accounting choices.The findings indicate that the implementation of these standards has the potential to enhance the relevance and transparency of financial reporting, particularly in providing focused disclosure on the company’s strategic decisions. Previous studies show that the value relevance of accounting information to stock prices improved following the adoption of IFRS 5/PSAK 58. Nevertheless, significant challenges remain, including fair value measurement issues, limited human resource competencies, and the risk of earnings management through asset misclassification.This study recommends stronger synergy between companies, regulators, auditors, and academic institutions to support the substantive implementation of IFRS 5/PSAK 58. When appropriately applied, these standards are expected to reinforce the integrity and efficiency of financial reporting in Indonesia and improve investor trust in financial disclosures. .